2016
DOI: 10.1111/1750-3841.13532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oak Chips on Evolution of Phenolic Compounds and Color Attributes of Bog Bilberry Syrup Wine During Bottle‐Aging

Abstract: This study investigated the evolution of phenolic compounds of bog bilberry syrup wine during a bottle-aging process, and further estimated the oak chip treatment on the wine color alteration. The wine was macerated with oak chips (2 or 5 g/L under light or medium toasting level) for 20 d and then bottle-aged for 6 mo. Results showed that the oak chip treatment significantly increased the content of phenolic compounds and enhanced the copigmented anthocyanin level before aging. It also resulted in an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 54 publications
2
13
1
Order By: Relevance
“…Malvidin‐3‐ O ‐glucoside, peonidin‐3‐ O ‐glucoside, and delphinidin‐3‐ O ‐glucoside were the most abundant individual anthocyanin compounds that accounted for 60.0, 17.2, and 12.5% of the total anthocyanin content, respectively. The overall phenolic profile of the bog bilberry wine was similar to our previous report (Liu et al, ).…”
Section: Resultssupporting
confidence: 90%
“…Malvidin‐3‐ O ‐glucoside, peonidin‐3‐ O ‐glucoside, and delphinidin‐3‐ O ‐glucoside were the most abundant individual anthocyanin compounds that accounted for 60.0, 17.2, and 12.5% of the total anthocyanin content, respectively. The overall phenolic profile of the bog bilberry wine was similar to our previous report (Liu et al, ).…”
Section: Resultssupporting
confidence: 90%
“…Mulberry wine color is mainly determined by anthocyanins in mulberry fruit. Regarding their structures, anthocyanins can be further divided into the free, copigmented, and polymerized anthocyanins (Boulton, ; Liu et al, ). It has been confirmed that free anthocyanins can be metabolized into copigmented and polymerized anthocyanins in wine during fermentation process (Boulton, ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been confirmed that free anthocyanins can be metabolized into copigmented and polymerized anthocyanins in wine during fermentation process (Boulton, ). Copigmented anthocyanins can improve the wine color through stabilizing anthocyanin structure, whereas polymerized anthocyanins can shift the wine color toward a yellowish hue (Bo, Fei, Zhou, Yue, & Duan, ; Boulton, ; Jacinto, Marta, Joséfederico, & Carlos, ; Liu et al, ). In the present study, the color contributions from the free anthocyanins were similar among these yeasts fermented mulberry wine samples (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that bottle‐aging at lower pH could lead to wine with more stable color and lower astringency (Mcrae, Kassara, Kennedy, Waters, & Smith, ). Additionally, incorporating oak chips into wine during bottle‐aging could result in a decrease in the phenolic compounds content in wine (Liu, Wang, Yuan, Ouyang, & Liu, ). Compared to bottle‐aging, tank‐aging process could provide wine with a micro‐oxygen condition.…”
Section: Introductionmentioning
confidence: 99%